Temporal trends of transmitted HIV drug resistance in a multinational seroconversion cohort. (14th January 2018) - Olson, Ashley; Bannert, Norbert; Sönnerborg, Anders; de Mendoza, Carmen; Price, Matthew; Zangerle, Robert; Chaix, Marie-Laure; Prins, Maria; Kran, Anne-Marte Bakken; Gill, John; Paraskevis, Dimitrios; Porter, Kholoud
Abstract : Background: The rate of transmitted drug resistance (TDR) may increase with wider use of antiretroviral therapy and can contribute to therapeutic failure. We analysed time trends in TDR among HIV seroconverters. Methods: Using CASCADE data of individuals with well estimated dates of HIV seroconversion, we examined HIV nucleotide sequences collected prior to antiretroviral therapy use from 1996–2012. All samples were taken within 12 months of testing HIV positive. Using logistic regression, we examined the association between TDR and year of seroconversion, adjusting for confounders. Results: Of 4717 individuals seroconverting between 1996 and 2012, median (IQR) age at seroconversion was 33 (27, 39) years. The majority (3839; 92%) were male, mainly exposed through MSM (3767; 80%), and infected with subtype B (3464; 73%). Overall, 515 (11%) individuals had at least one drug resistance-related mutation; 280 individuals with nucleoside reverse transcriptase, 185 with nonnucleoside reverse transcriptase, and 144 with protease inhibitor mutations. Estimated TDR prevalence was 19.4% (8.2, 36.0) in 1996, significantly decreasing to 8.5% (5.9, 11.9) in 2012 [odds ratio (OR; 95% confidence interval (CI)) = 0.92 (0.90, 0.95) per year increase]. Individuals exposed through sex between men and women were significantly less likely to have been infected with a drug-resistant strain [OR (95% CI) = 0.59 (0.41, 0.87) compared with MSM], and there was marginal evidence that sampling during acute infection was associated with higher odds of resistance [OR (95% CI) = 1.20 (0.97, 1.7), P = 0.093] compared with later sampling. Conclusion: TDR has decreased over calendar time although a significant proportion of new infections still carry resistance-related mutations. Abstract : Supplemental Digital Content is available in the text